Tea Extract Prevents Arsenic-mediated DNA Damage and Death of Murine Thymocytes in vitro - Akter, Masuma; Islam, Nafisa Nawal; Sumit, Ahmed Faisal; Ahsan, Nazmul; Hossain, Shahanoor; Ahmed, Mamun; Akhand, Anwarul Azim (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Groundwater contamination by arsenic has created a major health hazard in Bangladesh by affecting millions of people. In this study, we report cytotoxic effects of arsenic in primary culture of murine thymocytes and the counteractive actions of tea extract to reduce this cytotoxic effects. When murine thymocytes were incubated for shorter period (1 h) with higher concentrations (50 and 100 ?M) of sodium arsenite (NaAsO2), cell viability was decreased to 79.06 ± 0.52% and 62.53 ± 0.23%, respectively. In case of longer incubation (16 hrs) with a wide range of NaAsO2 concentration (1-100 ?M), cell viability was reduced from 89.30 ± 0.84% to 79.0 ± 0.52% by 1 ?M NaAsO2, and this reduction was continued with increasing concentration reaching to 29.60 ± 0.72% by 100 ?M. Tea is known to possess antioxidant property and we found that this tea extract reduced NaAsO2-mediated death of the cells in culture. After 16 h of incubation, the chromosomal DNA of 5 ?M NaAsO2-exposed cells was found degraded suggesting apoptotic death of the cells. Interestingly, this degradation of chromosomal DNA was blocked by tea extract. All of these results together suggest a future therapeutic application of tea extract to reduce or block arsenic toxicity. Dhaka Univ. J. Pharm. Sci. 14(1): 79-85, 2015 (June)